2005
DOI: 10.1001/archinte.165.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry as a Potential Screening Tool for Lower Extremity Arterial Disease in Asymptomatic Patients With Diabetes Mellitus

Abstract: Pulse oximetry of the toes seems as accurate as ABI to screen for LEAD in patients with type 2 diabetes. Combination of the two tests increases sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 26 publications
3
64
1
4
Order By: Relevance
“…without diabetes (6.39) which was consistent with previous studies involving similar populations [13,27,28]. The sensitivity of the ABI was poor in both groups, with (45.16%), and without diabetes (47.37%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…without diabetes (6.39) which was consistent with previous studies involving similar populations [13,27,28]. The sensitivity of the ABI was poor in both groups, with (45.16%), and without diabetes (47.37%).…”
Section: Discussionsupporting
confidence: 91%
“…The sensitivity of the ABI was poor in both groups, with (45.16%), and without diabetes (47.37%). This was slightly lower than previous studies [27,28] however this may have occurred as a result of the characteristic of the population we recruited. The participants in our study were older (mean age 72 and 74 years for participants with and without diabetes respectively), and there was also a large proportion of people with distally distributed PAD (36% in both groups).…”
Section: Discussioncontrasting
confidence: 58%
“…However, the sensitivity of the ABI test varied widely among previous published studies. ABI detection in diabetes and the elderly yielded lower sensitivity, 15 to 20% [13], 63% [14], 68% [15], 69.3% [16], and 70.6% [17], suggesting that the test may be affected by diabetes status and aging. And Feigelson et al [18] found that when they excluded patients with symptoms and signs of PAD, ABI values of less than 0.9 had a sensitivity of only 28.4%; and suggested that the ABI seems less accurate as a screening test in patients without symptoms or sings of PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly and diabetic patients constitute an increasing proportion of patients with PAD. The diagnostic performance of conventional techniques such as ABI, PVR, and Doppler ultrasound is reduced in these patients because of vascular noncompliance caused by medial arterial calcinosis, greater likelihood for diffuse or distal disease, and functional abnormalities of the microcirculation (15,16). For this reason, for any given reduction in ABI reduction, patients with DM tend to have more impairment in lower-extremity functional capacity than those without DM (17).…”
Section: Figure 1 Ceu Data From a Normal Subject And A Patient With Padmentioning
confidence: 99%